Preschool Children’s Audio–Visual Contents: Comparing Value, Educational and Narrative Approaches - Lorenzo Denicolai; Valentina Domenici (Cinergie)
With this contribution, we would like to examine some audio–visual narratives dedicated to the preschool age group (0–6 years). Our analysis is based on an interdisciplinary theoretical approach that draws on Film and Media Studies, dwelling on particular choices of audio–visual language, their educational impact, and their repercussion in an experiential key, also with some references to the most recent cognitive and neuro–filmological proposals. The article is divided into two parts, consequential and dependent. First, in addition to proposing a stylistic and content comparison of the cases examined and highlighting the messages conveyed, we focus on identifying two modes of genre production and their consequent functionality in proposing the educational and narrative approaches. On the one hand, we consider the television series, with its episodic development and its design for daily passage in the television schedule (we deal, in particular, with Bing and Tumble Leaf). This type of animation is functional in fostering the identification of the target audience in behavioural patterns linked to everyday life cases. On the other hand, we analyse two animated films, which are true ‘cinematographic’ texts (Room on the Broom; The Snail and the Whale), designed, however, for television and which respond more to the need to convey educational values of a general and human–identity nature. Secondly, we propose to analyse the same products in the light of Torben Grodal’s filmological theory, which provides interesting readings of a cognitive nature and which seems to us to help explain on which dynamics the objects examined can ‘act’ on young viewers.